Hallazgos de neuroimagen y desempeño ortográfi co de estudiantes con trastorno por défi cit de atención con hiperactividad según la semiología de los errores - Capellini, Simone Aparecida [UNESP]; Fusco, Natália [UNESP]; Oliveira Batista, Andrea [UNESP]; Moura, Regina [UNESP]; Lourencetti, Maria Dalva [UNESP]; Antunes dos Santos, Lara Cristina [UNESP]; Cervera-Mérida, José Francisco; Ygual-Fernández, Amparo (Elsevier, 2011)
Aim: To characterize, compare and classify the performance of students with attention deficit-hyperactivity disorder (ADHD) according to the semiology of errors and to describe the neuroimaging findings in these students. Methods: We evaluated 36 primary school boys and girls aged between 8 and 11 years old in the 3 rd to 5 th grades. The children were divided in two groups. Group I consisted of 18 students with an interdisciplinary diagnosis of ADHD (60% boys and 40% girls). Group II consisted of 18 children with good academic performance, paired by gender, age and grade with children in group I. The collective and individual versions of the Pro-ortografia spelling tests were applied. Results: Statistically significant differences were found in almost all the tests of the individual and collective versions of the spelling evaluation, with children with ADHD showing a higher average number of errors. Neuroimaging examinations indicated that 81% of the students in GI showed hypoperfusion in the frontal lobe, 7% had hypoperfusion of the thalamus and basal ganglia, 6% showed hypoperfusion in the basal ganglia only and 6% showed hypoperfusion in the left and right frontal lobes. Conclusions: Children with ADHD demonstrated poorer knowledge of the use of spelling rules in Brazilian Portuguese, which could be related to changes in blood flow in the frontal lobe, parietal lobe, thalamus and basal ganglia. These changes could cause a lack of attention, affecting phonological working memory and the planning of writing. © 2011 AELFA.
Neuroimaging findings and spelling performance in students with attention deficithyperactivity disorder according to the semiology of errors
Keywords: Attention deficit and hyperactivity disorder; Evaluation; Learning; Neuroimaging; Speech language therapy; Spelling